2016
DOI: 10.1021/acs.jctc.6b00703
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Differential Patterns of Drug Resistance in Influenza N1 and N2 Neuraminidase

Abstract: Neuraminidase (NA) inhibitors are used for the prevention and treatment of influenza A virus infections. Two subtypes of NA, N1 and N2, predominate in viruses that infect humans, but differential patterns of drug resistance have emerged in each subtype despite highly homologous active sites. To understand the molecular basis for the selection of these drug resistance mutations, structural and dynamic analyses on complexes of N1 and N2 NA with substrates and inhibitors were performed. Comparison of dynamic subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 53 publications
2
31
1
Order By: Relevance
“…1D) and result in reduced binding affinity between the side pocket and inhibitors, as was observed previously (15,(32)(33)(34). Previously, S246N/G and A246T substitutions were detected in association with NAI resistance in viruses of the N1 and N9 subtypes, respectively (15,32,35). The degree of inhibitor binding of residue 246 was higher for S246 of the N1 subtype than for A246 of the N2 subtype (35).…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…1D) and result in reduced binding affinity between the side pocket and inhibitors, as was observed previously (15,(32)(33)(34). Previously, S246N/G and A246T substitutions were detected in association with NAI resistance in viruses of the N1 and N9 subtypes, respectively (15,32,35). The degree of inhibitor binding of residue 246 was higher for S246 of the N1 subtype than for A246 of the N2 subtype (35).…”
Section: Discussionsupporting
confidence: 66%
“…The degree of inhibitor binding of residue 246 was higher for S246 of the N1 subtype than for A246 of the N2 subtype (35). Thus, resistance substitutions associated with S246 of the N1 subtype are predominantly detected compared with A246 of the other subtypes (35). However, we have found that an A246T substitution in the N9 subtype and an A246V substitution in the N6 subtype reduced ZA-mediated viral susceptibility.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…The experiments with the four neuraminidases were carried out in presence of the reference drug zanamivir. The catalytic residues within the active sites were identified as R118, R292 and R371 at subsite S1 and D151 at subsite S2, R152 at subsite S3, and E276 [ 9 , 17 , 36 , 37 ]. They are all interacting with zanamivir whose binding mode allows the drug to tightly attach to the viral enzyme and strongly inhibit the enzymatic activity, since the aforementioned residues are necessary for natural substrate recognition ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…The PDB entries were retrieved from the RCSB Protein Data Bank (RCSB PDB) [ 61 ]. The complete amino acid sequences of the viral neuraminidase were selected according to Prachanronarong [ 36 ] using the Influenza Virus Database ( ) [ 62 ]. The primary sequences were aligned through ClustalW, a web-based multiple sequence alignment tool ( ) [ 63 ].…”
Section: Methodsmentioning
confidence: 99%